Effect of build orientation on microstructure and tensile behaviour of selectively laser melted M300 maraging steel - Vishwakarma, J.; Chattopadhyay, K.; Santhi Srinivas, N.C. (Elsevier Ltd, 2020)
Additive Manufacturing (AM) is an emerging technology for fabrication of structural components, which refers to the processing through layer by layer addition of material using sliced CAD model of the desired geometry. Maraging steels are especially used in aerospace and tool industries due to their excellent combination of strength and fracture toughness. The present work aims at studying the effect of build orientation on microstructure and tensile behaviour of maraging steel (M300) processed by one of the AM techniques, namely, Selective Laser Melting (SLM). Initially, AM plates were processed in orientations of 0°, 45° and 90° and were further given solution treatment and aging. Measurement of density, surface roughness, hardness, residual stress and microstructural characterization of all samples were carried out and compared with those of conventionally melted (CM) samples. Transmission Electron Microscopy (TEM) confirmed the presence of Ni3Ti needle shaped precipitates and Fe2Mo globular precipitates after AM processing and also after heat treatment. Tensile testing of samples was conducted at a strain rate of 1 × 10−3 s−1. Better strength with reasonable ductility was observed in the samples built in 45° orientation compared to those at other build orientations and the properties in CM conditions. Solution treatment followed by aging decreased microstructural anisotropy caused by layer-wise effect due to laser processing. Surprisingly, most of the AM samples after heat treatment showed increase in strength without significant loss of ductility. Larger degree of work hardening and reversion of martensite to austenite might be the reasons for the observed behaviour. Typical ductile fracture featuring dimples due to microvoid coalescence were observed in all samples. Heat treatment not only improved tensile properties but also reduced anisotropy and residual stresses introduced during material processing. © 2020 Elsevier B.V.
Keywords: Maraging steel; Selective laser melting; Build orientation; Aging; Precipitates; Tensile behaviour